STATUS ANAK DALAM PERKAWINAN BEDA AGAMA DANA PERLINDUNGAN HAK-HAK ANAK - Annisa Dwi Savira (2023)
The purpose of this study was to analyze the status of children in interfaith marriages and the legal protection of children's rights in interfaith marriages. This research is qualitative and uses empirical legal methods. Researchs focused on the issue of the status of children from interfaith marriages and the legal protection of the rights of children from interfaith marriages. This research is descriptive in nature, presenting the latest facts in a systematic, factual, and correct manner using a normative legal approach using a statutory approach, so research is a legal product. In this study, researchers are looking for answers to the most important questions formulated, namely, analyzing how the status of children from interfaith marriages is determined and how legal protection of the rights of children from interfaith marriages is guaranteed. Providing certainty regarding the status of children from interfaith marriages who have nor received guarantees of state protection, both faorally and materially.